Electron and Photon Impact Ionization and Related Topics 2004 : Proceedings of the International Conference Louvain-la-Neuve, 1-3 July 2004 /: Proceedings of the International Conference Louvain-la-Neuve, 1-3 July 2004. (2005) - Piraux, B
No abstract available